Lactic acid bacteria methods and protocols - Kanauchi, Makoto ca. 20./21. Jh (Methods in Molecular Biology, 2019)
This detailed book provides a collection of protocols for numerous experimental approaches perfected by the authors for lactic acid bacteria (LAB) research. Split in to three parts, the volume delves into the identification and metabolism of LABs, the applications of the bacteria for the food industry, as well as healthy functions of LAB. Written for the highly successful Methods in Molecular Biology series, chapters include introduction to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and accessible, Lactic Acid Bacteria: Methods and Protocols serves as an ideal inspiration for many research efforts in the domains of food science and health science